Justicia de familia y victimización secundaria: un estudio aplicado con niños, jueces y abogados - Carretta, Francesco (2021)
Abstract: The International Convention on the Rights of the Child establishes their right to participate in all matters affecting them. Alongside, there is the widely studied phenomenon of secondary victimization (SV)in criminal justice. This article critically analyses the existence of SV in the context of family courts. In a qualitative study, the opinions of judges (n = 10), lawyers (n = 10) and children (n = 6) regarding child participation in family cases are explored. The analysis of the data provided by the interviews of judges and lawyers was made based on ten dimensions of analysis; and, in addition, the dogmatic method was used, with the description and comparative and critical analysis of the law, which was confronted with the aspects collected in the empirical work. The data analysis of the child participants was carried out by means of a categorical analysis based on three categories: to be informed, to be heard and to be considered in decision-making. Additionally, facilitating and hindering factors about their experience in family courts were extracted inductively. Results indicate that judges and lawyers show interest in child participation, but are limited by the view that there could be similar SV to that which exists in criminal proceedings. This contrasts with the perceptions of children, who indicate an interest in being informed and listened to, and suggests some elements for this experience to be favorable, such as the reduced presence of adults in the courtroom, getting to know the lawyers and judges beforehand, and the friendly treatment of children. Finally, suggestions are made to guarantee respect for the right to participation in an adequate context.